x2-9=0

Add 9 to both sides of the equation.

x2=9

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±9

Simplify the right side of the equation.

Rewrite 9 as 32.

x=±32

Pull terms out from under the radical, assuming positive real numbers.

x=±3

x=±3

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=3

Next, use the negative value of the ± to find the second solution.

x=-3

The complete solution is the result of both the positive and negative portions of the solution.

x=3,-3

x=3,-3

x=3,-3

Solve using the Square Root Property x^2-9=0